The lack of STEM vocations and gender gap in secondary education students - Hernández-Pérez, Mariana; Alonso-Sánchez, José A.; Hernández-Castellano, Pedro M.; Quevedo-Gutiérrez, Eduardo G. (Frontiers in Education, 2024)
The gender gap in STEM vocations among high school students still remains a troubling reality. Several studies indicate that students in general have less interest in science and technology subjects, and this disparity is even more distinguishable among female students. In fact, the aforementioned gender gap in STEM begins to manifest itself at an early age and worsens during adolescence. Some of the multiple causes include cultural factors, gender stereotypes and lack of female role models. Therefore, it is essential to promote gender equality and encourage inclusion and diversity in the educational environment as a key measure to reduce the gap. This is why in this study comprehensive research was carried out to analyze the factors that contribute to the gender gap in STEM careers. To this end, a survey was conducted of approximately one thousand secondary education students from a range of centres in the Canary Islands. The survey yielded insights into the direct influence of close references on students and the lack of female role models. This allowed the identification of effective measures to increase women's participation in these fields. One of the suggested solutions is the implementation of practical workshops, in which female figures play a key role. These workshops are used to demonstrate to students that there are numerous role models nearby who can motivate and encourage them to explore and develop their interest in the field of science and technology. By providing said opportunities and role models, our aim is to build their confidence and provide them with the necessary tools to take advantage of all the opportunities that the STEM field has to offer.